Transformational Leadership of Higher Education Library : Study at Library of Institut Pemerintahan Dalam Negeri Jatinangor Campus - Annisa Rahmadanita (JPUA: Jurnal Perpustakaan Universitas Airlangga: Media Informasi dan Komunikasi Kepustakawanan, 2022)
Background. This research is inspired by the results of previous research which stated that transformational leadership is an effective leadership style owned by a leader of a library organization. Therefore, the researcher examined practically related to this matter, especially in the application of the transformational leadership style applied by the leader of the IPDN Library, Jatinangor Campus. Research Methods. The research conducted presented qualitative data and researchers conducted interviews, observations and documentation in data collection. Data Analysis. Data analysis is carried out by reducing data, presenting data and drawing conclusions. Result: The researcher found that the application of the transformational leadership style at the IPDN Library of Jatinangor Campus was supported by the high commitment of the library staff. In addition, the leader of the IPDN Library of the Jatinangor Campus provides an open space for employees to be creative and provide suggestions, criticisms and ideas, especially in the decision-making process. Library leaders also routinely provide motivation and direction to instill the value of commitment to the staff of the IPDN Jatinangor Campus Library. Conclusion and Suggestion. Referring to these 8 indicators, there are 2 (two) indicators that require improvement the indicators of continuous improvement and the indicator of empowering organizational members. Researchers recommend that leaders of the IPDN Library Jatinangor Campus can take part in Leadership Training, especially those related to Higher Education Library Leadership. In addition, it is also hoped that the leader of the IPDN Library, Jatinangor Campus, can compile and carry out the division of duties and work of employees by adjusting to the functions and positions of library employees.